Estudo comparativo entre as soluções de preservação ViaSpan® e Celsior® utilizadas em transplante de fígado - Duca, William José (2009)
liver transplantation (OLT) is today the gold standard for the treatment of the end-stage liver disease. The preservation of graft is the cornerstone for the OLT with cadaveric donor. In this context, it is important to evaluate the effectiveness of different solutions used for it. Our objective was to compare the results of OLT, carried out with cadaveric donor, preserved with the solutions of preservation ViaSpan® or Celsior®. Casuistic and Method: we evaluated retrospectively 72 recipients of the OLT. Of these, 36 had their graft preserved with ViaSpanâ solution (Group A) and 36 with Celsiorâ solution (Group B) as follows: the donor was perfused in situ of 1000 ml in the portal vein of ViaSpanâ or Celsiorâ and 3000 ml of Euro-Collins in aortic artery; in the table managed ViaSpanâ or Celsiorâ 500 ml in the portal vein, 250 ml in hepatic artery and 250 ml in the biliary duct. The following variables in groups A and B were evaluated: cost of the solutions, characteristics of the donors, characteristics of the recipients, intraoperative details, reperfusion injury and esteatose of graft with biopsy carried out after the reperfusion. As results of the OLT were evaluated: grafts with primary nonfunction (PNF), initial poor function (IPF), rejection, complications of the biliary duct, complications of the hepatic artery, retransplantation, follow up of the receiver in the first year after the OLT. Results: bigger warm ischemia and duration of surgery in group A (p= 0,002 and 0.001 respectively). The cost of the Celsior solution was lower (less than U$ 266.00 per litre). The remaining: characteristics of the donors, characteristics of the recipients, reperfusion injury, steatosis, PNF, PDF, rejection, retransplantation and recipients survival had not shown significant difference in statistics. Stenosis of the biliary duct was 3 cases (8.3%) in group A and 8 (22.2%) in group B (p= 0.19) and thrombosis of the hepatic artery were 4 cases (11.1%) in group B and none in group A (p= 0.11). Conclusion: the result of OLT, performed with cadaveric donor, preserved with ViaSpanâ or Celsiorâ solutions was similar. However we observe a trend of bigger number of stenosis of the biliary duct and thrombosis of the hepatic artery in the recipients of agencies preserved with the Celsiorâ solution. Thus, we believe that more research is necessary to clarify this relation.